ZEOLITE ADSORPTION MEASUREMENT TEST RESULTS WITH VARIOUS DATES OF CURRUMIN AS ADSORTATE - Gina Sajida (Jurnal Kimia Fullerene, 2022)
The purpose of this study was to analyze and measure the intensity of light obtained through an LED flashlight emitted by a solution of curcumin and zeolite from the adsorption process. In addition, this study also aims to determine the appropriate isotherm model for this experiment. Variations in the dose of zeolite were taken to find out the big difference using the Lux Light Meter application. The method used is an experimental method, where the process that occurs is the light source from the sender stored in the cardboard will pass through a gap and also the bottle that has been filled with a solution of curcumin and zeolite. Then the light beam will be captured by the Lux Light Meter so that the value will be obtained. The results showed that zeolite carbon as an adsorbent was able to absorb turmeric or curcumin solution well. The equilibrium model used is Langmuir, Freundlich, Temkin, Dubinin-Radushkevich, Flory Huggins, Flower-Guggenheim, Hill-Deboer, Jovanovic, Harkin-Jura, and Halsey. The Langmuir, Freundlich, and Halsey isotherms show success in describing this adsorption process.